Waste-to-Profit Transformation: Innovative Strategies for Waste Recycling as a Sustainable Source of Income - Ismail, Ismail; Marhati, Marhati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The growing waste management problem, especially in developing countries, poses significant environmental, social, and economic challenges. This qualitative study, using an ethnographic approach, investigates community perceptions of waste, recycling’s potential as an income source, and innovative recycling strategies in Bone Regency, South Sulawesi. Bone Regency, a region with limited waste infrastructure and high levels of waste pollution, faces unique social and economic challenges in sustainable waste management. Data were collected through in-depth interviews, participant observations, and document analysis involving community members and the Community-Based Solid Waste Management (CBSWM) initiative. Data analysis involved thematic coding to identify key patterns in perceptions, challenges, and outcomes. The findings reveal that community perceptions of waste shifted positively as they recognized its economic potential. Innovative strategies, including community-based waste management and social entrepreneurship, successfully generated income and promoted sustainable practices. Products such as organic compost, recycled plastic crafts, and construction materials demonstrate economic opportunities, though market access and scalability remain critical challenges. The study concludes that infrastructure improvements, expanded market opportunities, and policy support are essential for sustainable waste management in the Bone Regency. Future research should explore scalable recycling models, environmental impacts, and policy implications to support broader applications in similar regions.